Effects of the synthesis coating parameters for metal bipolar plates - Nur Fawwaz Asri,; Teuku Husaini,; Abu Bakar Sulong,; Majlan, Edy Herianto (Penerbit Universiti Kebangsaan Malaysia, 2020)
Metallic bipolar plates tendency to have high contact resistance, but also very susceptible to corrosion. This may decrease in the performance of fuel cells after several times of usage in fuel cell applications. Research has shown that after a metal plate was coated, the characteristic of materials dependent on the type, composition of the coating materials and the method. This study determines design of coating parameters including gas flow rate, DC power, and deposition time of coating for metal bipolar plates, which can be an indicator of the suitability of these plates for use as bipolar plates in proton exchange membrane fuel cell (PEMFC) applications. The aim of this research was to obtain a limitation range value of parameters that can be used as a standard for the use of metal plates as bipolar plates. The optimization parameters designed by Taguchi are used to determine the characteristics of interfacial contact resistance (ICR) and corrosion current density (Icorr). The integration of the Taguchi method with simulation can show the optimal design parameters of the coating on the various materials use. The optimization feature based on Taguchi is applied to ICR and Icorr values, to determine the feasibility of metal plates as potential bipolar plates in PEMFC.